Hip joint contact loads in older adults during recovery from forward loss of balance by stepping. Issue 13 (6th September 2016) - Graham, David F.; Modenese, Luca; Trewartha, Grant; Carty, Christopher P.; Constantinou, Maria; Lloyd, David G.; Barrett, Rod S.
Abstract: Hip joint contact loads during activities of daily living are not generally considered high enough to cause acute bone or joint injury. However there is some evidence that hip joint loads may be higher in stumble recovery from loss of balance. A common laboratory method used to evaluate balance recovery performance involves suddenly releasing participants from various static forward lean magnitudes (perturbation intensities). Prior studies have shown that when released from the same perturbation intensity, some older adults are able to recover with a single step, whereas others require multiple steps. The main purpose of this study was to use a musculoskeletal model to determine the effect of three balance perturbation intensities and the use of single versus multiple recovery steps on hip joint contact loads during recovery from forward loss of balance in community dwelling older adults ( n =76). We also evaluated the association of peak hip contact loads with perturbation intensity, step length and trunk flexion angle at foot contact at each participant׳s maximum recoverable lean angle (MRLA). Peak hip joint contact loads were computed using muscle force estimates obtained using Static Optimisation and increased as lean magnitude was increased and were on average 32% higher for Single Steppers compared to Multiple Steppers. At the MRLA, peak hip contact loads ranged from 4.3 to 12.7 body weights and multiple linear stepwise regression further revealed that initial lean angle, step length and trunk angle at foot contact together explained 27% of the total variance in hip joint contact load. Overall findings indicated that older adults experience peak hip joint contact loads during maximal balance recovery by stepping that in some cases exceeded loads reported to cause mechanical failure of cadaver femurs. While step length and trunk flexion angle are strong predictors of step recovery performance they are at best moderate predictors of peak hip joint loading.